2022
DOI: 10.1098/rstb.2021.0025
|View full text |Cite|
|
Sign up to set email alerts
|

Managing human-mediated range shifts: understanding spatial, temporal and genetic variation in marine non-native species

Abstract: The use of molecular tools to manage natural resources is increasingly common. However, DNA-based methods are seldom used to understand the spatial and temporal dynamics of species' range shifts. This is important when managing range shifting species such as non-native species (NNS), which can have negative impacts on biotic communities. Here, we investigated the ascidian NNS Ciona robusta , Clavelina lepadiformis , Microcosmus squamiger a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 107 publications
0
11
0
Order By: Relevance
“…Furthermore, invasive species are a major threat to biodiversity worldwide [76,77]. Invasive species often exhibit higher plasticity than non-invasive species do [78][79][80] and it has been suggested that plasticity may be a key factor governing invasion success [78,80,81].…”
Section: (D) Management and Conservation Applicationsmentioning
confidence: 99%
“…Furthermore, invasive species are a major threat to biodiversity worldwide [76,77]. Invasive species often exhibit higher plasticity than non-invasive species do [78][79][80] and it has been suggested that plasticity may be a key factor governing invasion success [78,80,81].…”
Section: (D) Management and Conservation Applicationsmentioning
confidence: 99%
“…Niche limits may be exceeded locally, within the species’ range, as well as at its geographical limits [ 27 ]. Understanding these ecological limits is critical for the management of range change, as discussed here for non-native marine species [ 18 ].…”
Section: Single Species Perspectivesmentioning
confidence: 99%
“…Holman et al . [ 18 ] compare current and historical distributions of non-native ascidian species along the coast of South Africa using both genetic and inventory data. They also evaluate the usefulness of environmental DNA (eDNA) in addressing this type of question.…”
Section: Conservation and Management Implications And Possible Actionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Range expansion can cause surfing of underdominant alleles [ 7 ]. Finally, three contributions move towards management considerations, starting with biophysical modelling of dispersal [ 8 ] and reconstruction of invasion history [ 9 ] and then considering management of human-mediated range change [ 10 ].…”
mentioning
confidence: 99%